2014
DOI: 10.1007/s00425-014-2203-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and analysis of Catharanthus roseus RLK1-like kinases in rice

Abstract: A genome-wide survey of Catharanthus roseus receptor-like kinase1-like kinases (CrRLK1Ls) in rice revealed that the pattern of expression by some CrRLK1Ls is controlled by drought or circadian rhythms. This is probably accomplished through the functioning of Gigantea ( OsGI ). Such findings provide a novel angle for using CrRLK1Ls to study the drought-stress response and circadian regulation. The 17 CrRLK1L members of a novel RLK family have been identified in Arabidopsis. Each carries a putative extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 52 publications
0
40
0
Order By: Relevance
“…To examine these data, we used the Affy package encoded by R language to normalize the signal intensity and then transformed them into log 2 values. The normalized data, with averaged Affymetrix anatomical meta-expression data, were then used for further investigations, e.g., heatmap construction, and identification of the late-pollen-preferred genes [52].…”
Section: Meta-expression Analysismentioning
confidence: 99%
“…To examine these data, we used the Affy package encoded by R language to normalize the signal intensity and then transformed them into log 2 values. The normalized data, with averaged Affymetrix anatomical meta-expression data, were then used for further investigations, e.g., heatmap construction, and identification of the late-pollen-preferred genes [52].…”
Section: Meta-expression Analysismentioning
confidence: 99%
“…Beyond the initial identification of CrRLK1 (Schulze-Muth et al, 1996), phylogenomics identified 16 CrRLK1L homologs with Gigantea-mediated circadian regulation of their expression in Oryza sativa (Nguyen et al, 2014). Secondly, Niu et al (2016) described ∼40 CrRLK1L family members in diploid cotton species, six of which are linked to fiber development.…”
Section: An Evolutionary Perspective Of the Crrlk1l Subfamilymentioning
confidence: 99%
“…We recently suggested putative functions for most members of several gene families based on the integration of experimental and meta-expression data (Jung et al 2013; Jin et al 2012; Nguyen et al 2013; Nguyen et al 2014; Nguyen et al 2015). Applying a similar approach with the rice PRX family could help elucidate the functions of those members.…”
Section: Introductionmentioning
confidence: 99%